One Bread, One Body: Exploring Cultural Diversity in Worship - Hawn, C. Michael (Rowman & Littlefield Publishers, 2003)
As a troubadour for global music and an instigator of cross-cultural worship for more than 15 years in a variety of denominational settings, including congregational, national, and international venues, Michael Hawn has observed many faithful people who find that a taste of Pentecost in worship is refreshing and invigorating. In One Bread, One Body: Exploring Cultural Diversity in Worship, Hawn seeks to help bridge the gap between the human tendency to prefer ethnic and cultural homogeneity in worship and the church's mandate to offer a more diverse and inclusive experience. He offers a rainbow vision of the universal church where young and old joyfully and thoughtfully respond to the movement of God's Spirit in multicultural worship. Hawn and four colleagues from Perkins School of Theology in Dallas formed a diverse team in ethnicity, gender, academic field of study, and denominational affiliation to study four United Methodist congregations in the Dallas area that are grappling with cross-cultural ministry. Their four case studies illustrate both the pain and the possibilities encountered in capturing the Spirit of Pentecost in worship. Hawn also offers a concise and practical theological framework as well as numerous strategies and an extensive bibliography for implementing "culturally conscious worship." This book is invaluable for congregations that want to undertake the hard work of cross-cultural worship.